Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/molecules25092219
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin Loaded Poloxamer Thermosensitive Hydrogels: Chemical, Pharmacological and Biological Evaluation

Abstract: (1) Background: doxorubicin is a potent chemotherapeutic agent, but it has limitations regarding its side effects and therapy resistance. Hydrogels potentially deal with these problems, but several characterizations need to be optimized to better understand how hydrogel assisted chemotherapy works. Poloxamer 407 (P407) hydrogels were mixed with doxorubicin and physico-chemical, biological, and pharmacological characterizations were considered. (2) Methods: hydrogels were prepared by mixing P407 in PBS at 4 °C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…The pH value of this formulation was 6.5, which is suitable for skin administration and suggests a non-irritating effect. Regarding the morphological structure (Figure 2), SEM micrographs of PF-NLCs-F127 hydrogel revealed the typical porous structure that characterizes Pluronic gels [29]. Moreover, PF-NLCs of nanometric size and spherical shape dispersed inside the hydrogel without showing aggregation (none was observed).…”
Section: Discussionmentioning
confidence: 98%
“…The pH value of this formulation was 6.5, which is suitable for skin administration and suggests a non-irritating effect. Regarding the morphological structure (Figure 2), SEM micrographs of PF-NLCs-F127 hydrogel revealed the typical porous structure that characterizes Pluronic gels [29]. Moreover, PF-NLCs of nanometric size and spherical shape dispersed inside the hydrogel without showing aggregation (none was observed).…”
Section: Discussionmentioning
confidence: 98%
“…In this study, as observed under the stereomicroscope, the carbonation reaction of eutectic effervescent tablets gradually occurred upon immersion in the medium. This is explained by gelling capabilities of P407, which can retard the breakdown of the eutectic effervescent tablet [54]. For the results of mathematical model fitting, all formulations exhibited the tendencies of Peppas-Sahlin in which the R 2 values were close to 1.0.…”
Section: In Vitro Disintegration Of Eutectic Effervescent Tabletsmentioning
confidence: 89%
“…192 Several poloxamers are commercially available, differing in composition and molar mass (MM). 34,[192][193][194] The most commonly used poloxamer in TRG-related studies is poloxamer 407 (Pluronic® F127, MM ≈ 12.6 kg mol −1 and EG 70 wt%), 6,[43][44][45][46][47][48][49][50][51][52][53][54][55][56]195,196 as this poloxamer gels at lower temperatures and concentrations compared to the other members of the family. 34 More specifically, it has been reported that poloxamer 407 gels at 12.6 w/v% in phosphate buffered saline (PBS), when purified appropriately, while gelation is not observed when the concentration is reduced to 11.6 w/v%.…”
Section: Poloxamer Basedmentioning
confidence: 99%
“…without any polymer additives that would act as gelation modifiers, were applied in vivo have been reported in the literature. 6,[43][44][45][46][47][48][49][50][51][52][53][54][55][56]195,196 Most of the studies have used solutions of poloxamer 407 at 20 w/w% and higher, due to the higher stability and strength of the gel; however, a few studies have attempted the application at 15 w/w%. In TE, the gel was used to replace the nucleus pulposus, which acts as a shock absorber, in the intervertebral disc in dogs, and it was proven to be effective in resisting the strain applied for at least a period of 3 months.…”
Section: Poloxamer Basedmentioning
confidence: 99%